The quality of the administrative service influences the satisfaction of the students of the graduate school, UNHEVAL - Huánuco, year 2017 - Accilio-Tucto, Edver (2019)
The objective of the research was to determine the influence of the Quality of Administrative Service on the satisfaction of the students of the Graduate School, UNHEVAL - Year 2017. The type of research was applied. The research design was non-experimental. The population of the present research work consisted of 1082 students of the Graduate School - UNHEVAL of the year 2017. The sample of this research work consisted of 284 students of the Graduate School, UNHEVAL - Year 2017. The results arrived at the present research work showed that the quality of administrative service influences the satisfaction of students of the Graduate School, UNHEVAL - Year 2017, with a level of significance of 0.05 and a level of confidence of 95% with the data collected of empirical reality. The significance test carried out under Statistical F and Probability (statistical F), shows that the variables are significant individually and jointly are also significant. The values ​​are respectively 163.685 and 0.00, which allow rejecting the null hypothesis (that all the coefficients are simultaneously less than or equal to zero). The conclusion reached in the research was: The tangible elements influence the satisfaction of the students of the UNHEVAL Graduate School directly. The attention of the Library and Secretary influences the satisfaction of the students of the Graduate School of the UNHEVAL in a direct way, with a level of significance of 0.05 and a level of confidence of 95% with the data collected from the empirical reality.